Seleksi Staff IT Menggunakan Metode Preference Selection Index (PSI) - Iwan Adhicandra; Jeperson Hutahaean; Rima Ruktiari Ismail; Neni Mulyani; Novrini Hasti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
To get the right employees and in accordance with the criteria of the company or agency is certainly not easy. Therefore, to get the employees desired by the company or agency, a selection of prospective IT staff in a company is needed so that later the company or agency will get competent IT staff in accordance with their field. The large number of applicants in the company makes it difficult for companies to experience obstacles and difficulties in choosing prospective IT staff. In the selection process, it is often influenced by subjective factors that can lead to the election of incompetent employees. For this reason, an information system is needed that can help companies in selecting prospective IT staff. This system is known as a decision support system. for this study, the Preference Selection Index method is used based on several studies that have been published. The final results of the calculation were obtained the names of candidates in order from rank 1 to 10, namely: Fani, Bunga, Agus, Evan, Putra, Jaka, Dani, Andi, Citra and Intan